The Impact of Enterprise Social Media Use on Employee Innovation Behaviour - Chi , Huizhong; Yang, Huixin (Transformations In Business & Economics, 2026)
This study employs the survey questionnaire method to empirically investigate how enterprise social media affects the innovation behaviour of employees in China-based enterprises, examining the roles of team climate and leader-member exchange. Accordingly, the study participants were recruited through the Credamo platform. By applying the social exchange theory, the study findings indicate that leader-member exchange and team climate constitute substantial mechanisms that influence the effects of enterprise social media on employees’ innovation behaviour. The use of enterprise social media facilitates interaction between leaders and subordinates, stimulating employees to foster job commitment and innovative behaviour, and optimising organisational performance. As a result, innovative behaviour is supported through optimised social exchange processes in the workplace. Furthermore, this research also confirms the profound moderating effects of enterprise social media intensity on the relationship between the use of enterprise social media and employee innovation behaviour. Reportedly, leader-member exchange bolsters the effect of employee innovation behaviour by augmenting the intensity of enterprise social media. Thus, this study offers valuable insights into the influence of enterprise social media use on social exchange relationships and employee innovation behaviour.